2012
DOI: 10.2106/jbjs.k.01726
|View full text |Cite
|
Sign up to set email alerts
|

Forceps Reduction of the Syndesmosis in Rotational Ankle Fractures

Abstract: Clamp placement in the neutral anatomical axis reduced the syndesmosis most accurately in our cadaveric model, although slight overcompression was frequently observed. Placing the clamp obliquely malreduced the unstable syndesmosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(139 citation statements)
references
References 16 publications
5
123
0
11
Order By: Relevance
“…There is substantial anatomic variability in the tibiofibular incisure (Elgafy et al 2010, Mukhopadhyay et al 2011, Lepojärvi et al 2013, and the risk for syndesmotic malreduction is especially high in patients with flatter tibiofibular articulations (Elgafy et al 2010). In these patients, the vector of the reduction clamp is critical for appropriately positioning the fibula within the tibiofibular incisure during syndesmotic reduction (Phisitkul et al 2012).…”
Section: Syndesmosismentioning
confidence: 99%
“…There is substantial anatomic variability in the tibiofibular incisure (Elgafy et al 2010, Mukhopadhyay et al 2011, Lepojärvi et al 2013, and the risk for syndesmotic malreduction is especially high in patients with flatter tibiofibular articulations (Elgafy et al 2010). In these patients, the vector of the reduction clamp is critical for appropriately positioning the fibula within the tibiofibular incisure during syndesmotic reduction (Phisitkul et al 2012).…”
Section: Syndesmosismentioning
confidence: 99%
“…7 Ideally, the clamp and screw would both be placed along the neutral axis to avoid malreduction. This problem with malreduction caused by off-axis clamp and screw placement has been further demonstrated by Phisitkul et al 8 Miller and colleagues recommended more anterior screw trajectory for a screw through a posterior plate, and a more posterior trajectory for a lateral plate. Needleman 9 has described a glide path technique that uses direct K wire reduction along the neutral anatomic axis to ultimately guide screw fixation along the same axis.…”
Section: Historical Perspectivementioning
confidence: 91%
“…100 Another cadaveric study showed that placing a clamp in the neutral anatomic axis reduced the syndesmosis most accurately, although minimal overcompression was observed. 101 The authors use a clamp in some situations; however, they have used manual reduction and stabilization using the thumb to generate the reduction force. This is an emerging technique that may decrease the risk of malreduction associated with a clamp.…”
Section: Clamp Placementmentioning
confidence: 99%